RANCANG BANGUN MEDIA PEMBELAJARAN BERBASIS ANDROID (SMART APP CREATOR) PADA MATA PELAJARAN SISTEM ADMINISTRASI JARINGAN DI SMK ULIL ALBAB - mahfud mahfud; Indra Maulana; Dirno Dirno (Institut Pendidikan dan Bahasa Invada, 2020)
Student learning outcomes are influenced by two factors, namely internal factors and external factors. Internal factors come from within students and external factors that come from outside students. Internal factors such as students' abilities, interests and motivation to learn, while external factors such as environmental conditions, schools and learning quality. The use of media in learning can help the limitations of educators in conveying information as well as the limitations of class hours. The media serves as a source of information on learning materials and as a source of practice questions. The quality of learning is also influenced by individual differences of students, both differences in learning styles, differences in cognitive abilities, differences in learning speed, and differences in background. This research and development aims to develop learning media for Android-based network server administration on basic network server administration materials, knowing the process of designing learning media developed, and making learning media developed using smart apps creators. There is no android-based learning media in the subject of network server administration. From the results of the preliminary study, it can be illustrated that the learning media used in the learning process still use paper and print media. Student learning outcomes are still far from expectations (KKM). Software development uses the waterfall model development method. In the waterfall there are several main stages that describe software development activities. The reason for using the waterfall method is because the stages in system development in the waterfall model are clearly structured.